Analisis Sistem Akreditasi Program Studi di Universitas Jambi - Aryani, Reni; Mauladi, Mauladi; Saputra, Edi; Noverina, Yolla (JUSS (Jurnal Sains dan Sistem Informasi), 2018)
Jambi University as an organizer Tridharma college should make the process of evaluation and comprehensive assessment for its commitment to quality and implementation capacity Tridarma college program, in order to realize its vision and mission. Through the assistance efforts of accreditation granted by the Quality Assurance Agency, the University of Jambi sought to conduct a good evaluation and assessment of the commitment of all the courses in the shade in the accreditation. However, in the process, there are still obstacles, which are not already own standard operating procedures (SOP) facilitation of accreditation at Jambi University. There are also constraints on all business processes of accreditation systems that are managed by conventional means and are not yet integrated with information systems. So it takes an act of proper analysis to see the flow of the process of implementing a system of accreditation at Jambi University. Results obtained from this research activity is the recommendation mapping technology needs in the form of an integrated